Penerapan Soil-Water Characteristic Curve (SWCC) Pada Pemodelan Tanggul Menggunakan Material Lumpur Sidoarjo Yang Distabilisasi Dengan Kapur - Cupasindy, Dyah Ayu Rahmawati; Soemitro, Ria Asih Aryani; Indarto, Indarto; Satrya, Trihanyndio Rendy (Jurnal Aplikasi Teknik Sipil, 2020)
This research is a modeling geotechnical auxiliary programs with secondary data processing from previous research. The purpose of this modeling is to analyze the stability of the embankment due to the application of the matric suction value on the Soil-Water Characteristic Curve (SWCC) to see the effect of changes in water content in the lime stabilized LuSi material which can be used as embankment embankment material. The matric suction value used with a value of 1-480 kPa greatly affects the stability of the embankment and the relation to the value of the safety value. The effect of groundwater level elevation gives the value of the safety factor of the embankment in a safe condition with a range of 1.3-2.6 at the variation in height (6-10 m) and embankment slope (1: 1, 1: 1.5 and 1: 2). The effect of the height of the LuSi sediment provides a value of the safety factor of the embankment in a safe condition with a range of 1.25 - 2.12 on a 1: 2 slope at height (1-7 m). The rate of immediate settlement on the embankment ranges from 14 - 40 cm every 200 days for variations in height (6-10 m) and embankment slope (1: 1, 1: 1.5 and 1: 2).